Hepatoprotective and Nephroprotective Potentials of Aqueous Leaves ExtractofLimoniaacidissimain Phenylhydrazine-Induced AnaemicWistar Rats - T., Nwauche, K.; C, Anacletus, F.; M, Ugwu, G. (Asian Journal of Pharmaceutical Research and Development, 2019)
Bioactive composition of Limoniaacidissima leaf and liver enzyme levels and kidney status ofphenlyhydrazine (phz)-induced anaemicwistar rats were investigated. A total of forty two (42) wistar rats weighing between 150-200g were used. The animals were randomly divided into seven (7) groups of six rats each. Folic acid and vitamin B12 were used as reference drugs. Aqueousextract of Limoniaacidissima leaves was administered to the rats for four (4) weeks period.Qualitative phytochemical analysis on the dry leaf samples revealed the presence of the following in low abundance: alkaloid, saponins, cardiac glycoside, steroids, phenols, terpenoids and proteins while flavonoids were in high abundance. A significant increase (p<0.05) was observed in the activities of serum alanine transaminase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP) in thephenylhtdrazine-inducedanaemic non- treated groups in comparison to normal control. There was a significant increase (p<0.05) in urea, creatinine, potassium and sodium levels in the phenylhydrazine-induced anemic non- treated rats compared to the normal control. The other groups treated with aqueous leaf extract of Limoniaacidissimasubsequently ameliorated these effects on the liver and kiney markers. Vitamine B12 and folic acid also reversed these effects on the liver enzymes and kiney markers.This outcome illustrates that the aqueous extract of the leaf of Limoniaacidissimapossess a protective potentials on the liver and kidney of phenylhydrazine- induced wistar rats.